The comparative description of the consonants j (й), k, q (қ) in Kazakh, Turkish and Uzbek languages. (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted to one of the actual, scientific theory, critical issues challenging problems in the history of formation of the individual in writing – literary languages. Studied by the system according to a comparative study to establish the basic phonetic patterns of three genetically related groups of Turkic language family: kipchak, karluk and oguz. This problem is especially in such a plan has not been considered, and it is fraught with many previously undiscovered and unexplored phonetic-phonologicalphenomena, comparative study of which is of undoubted scientific and practical interest, for a total turkic, and for each of the studied languages. It is known that each of the modern Turkic languages was formedas a result of a long process of structural development, mining and continuous improvement of literary (written spelling, speech, etc.) norms. In this process, perhaps one of the main factors of formation oflanguage, its own rules and combatant elements becomes elected and he developed the same phonetic system. Phonetic structure of any language is composed according to a coordinated and closely related to one another phonetic and phonological phenomena that gradually become stable, stable rules and regularities of the language.
Keywords: consonants; phonetic patterns; the system; talk; Kazakh; Turkish; Uzbek; comparison; borrowing